THE CONSEQUENCES OF AIRBORNE INFECTIONS FROM A SOCIAL AND ECONOMIC PERSPECTIVE - Talat T. Mamatkulov; Ulbolgan D. Utepbergenova (Central Asian Journal of Medicine, 2025)
In this article, the focus is set on the sociological aspects of airborne infection alongside other social and economic impacts. The article summarizes TB, flu, COVID-19, and their spread patterns in the region and Uzbekistan in particular. It analyzes the countermeasures available for these diseases and their current treatment strategies while auditing Uzbekistan’s situation regarding airborne infections. Moreover, it provides social and economic consequences in terms of lost productivity, health care costs as well as stigma and social isolation, underlined through direct quotations and comparison tables that substantiate the argument. It highlights the lack of focus on the sociological side and preventive measures necessary to contain the infection.